Dispute Resolution in Arbitration Law Reviewed from Law No.30 of 1999 - Muhammad Ihsan; Muhammad Zailani Al Husaini; Fadillah alfattah; Muhammad Ikhlas Bin Rosele (Jurnal Cendikia ISNU SU, 2024)
Out-of-court dispute resolution is an important alternative in the Indonesian legal system, especially through the arbitration mechanism regulated by Law No. 30 of 1999. This article examines dispute resolution through arbitration and alternative dispute resolution (APS), emphasizing key principles such as the autonomy of the parties, the finality of the award, and the prohibition of court interference. This research uses a qualitative approach with a literature review that highlights the role and implementation of arbitration in a wide range of disputes, including civil and criminal cases. The findings show that although arbitration has advantages such as speed and confidentiality, challenges remain, particularly in terms of the implementation of arbitration awards in Indonesia. In addition, the application of arbitration principles, such as freedom of choice of law and the place of arbitration, requires strengthening regulations in order to ensure legal certainty. This article also highlights the potential for resolving criminal disputes through criminal mediation based on the values of restorative justice, but still requires clearer regulations to support this practice.